2012
DOI: 10.1007/s00330-012-2595-y
|View full text |Cite
|
Sign up to set email alerts
|

Helical CT-enteroclysis in the detection of small-bowel tumours: a meta-analysis

Abstract: Our meta-analysis confirms that helical CT-enteroclysis has high degrees of sensitivity and specificity for small-bowel tumour detection. However, our findings reinforce the need for more standardised individual studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 39 publications
0
23
0
2
Order By: Relevance
“…For sporadic lesions, small bowel follow-through has a sensitivity of approximately 50%, which is equivalent to CT performed without small bowel distension (Soyer et al, 2011;Maglinte, 2006Maglinte, , 2005. By contrast, CT-enteroclysis has a sensitivity of 85-95% and a specificity of 90-96% (Boudiaf et al, 2004;Pilleul et al, 2006;Soyer et al, 2013a). Similarly, MR-enteroclysis has a sensitivity of 86-91%, a specificity of 95-98%, and an accuracy of 97% (Masselli et al, 2009;Van Weyenberg et al, 2010).…”
Section: Imaging Findingsmentioning
confidence: 88%
“…For sporadic lesions, small bowel follow-through has a sensitivity of approximately 50%, which is equivalent to CT performed without small bowel distension (Soyer et al, 2011;Maglinte, 2006Maglinte, , 2005. By contrast, CT-enteroclysis has a sensitivity of 85-95% and a specificity of 90-96% (Boudiaf et al, 2004;Pilleul et al, 2006;Soyer et al, 2013a). Similarly, MR-enteroclysis has a sensitivity of 86-91%, a specificity of 95-98%, and an accuracy of 97% (Masselli et al, 2009;Van Weyenberg et al, 2010).…”
Section: Imaging Findingsmentioning
confidence: 88%
“…The combination of small bowel distension with negative contrast and mural enhancement with intravenous contrast allows detailed assessment of the small bowel wall 5. A recent meta-analysis (n=696) reported that CT enteroclysis had a per-patient pooled sensitivity of 92.8% for SBTs 6. There is, however, a relative paucity of studies looking at CTE detection of SBTs.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostics of small intestine diseases may include computed tomography (CT) enterography/enteroclysis or magnetic resonance imaging (MRI) enterography/ /enteroclysis, which locate the primary focus in the small intestine in approximately 90-97% of patients [41][42][43]. For the follow-up concerning small intestine diseases, CT or MRI enterography should be applied.…”
Section: Primary Tumour Locationmentioning
confidence: 99%